Analysis of The Harmfulness of Tobacco Smoking Through the Reliability Coefficient - Bahramov Rustam Rakhmatullayevich; Haydarova Naila Pardaboy qizi; Husanova Mehribon Sherzod qizi; Mahmudova Nilufar Husniddin qizi (International Journal of Medical Sciences And Clinical Research, 2025)
We know that smoking is harmful to human health. But it is very difficult for us to follow this, because a person can find himself in different situations. There are happy days, there are anxious days. Then we smoke tobacco to distract ourselves, and every time such a situation occurs, we start smoking tobacco and we develop a tendency to do so.